2023
DOI: 10.3389/fpsyg.2023.1086699
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences moderate effects in an Unusual Disease paradigm: A psychophysical data collection lab approach and an online experiment

Abstract: We report two studies investigating individual intuitive-deliberative cognitive-styles and risk-styles as moderators of the framing effect in Tversky and Kahneman's famous Unusual Disease problem setting. We examined framing effects in two ways: counting the number of frame-inconsistent choices and comparing the proportions of risky choices depending on gain-loss framing. Moreover, in addition to gain-loss frames, we systematically varied the number of affected people, probabilities of surviving/dying, type of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…However, investigation of the relationship between the need for cognition and the framing effect has shown mixed results. While some studies indicated that the need for cognition moderates framing effects, others did not identify a significant relation (Wyszynski & Diederich, 2023).…”
Section: Need For Cognition and Numeracymentioning
confidence: 99%
See 1 more Smart Citation
“…However, investigation of the relationship between the need for cognition and the framing effect has shown mixed results. While some studies indicated that the need for cognition moderates framing effects, others did not identify a significant relation (Wyszynski & Diederich, 2023).…”
Section: Need For Cognition and Numeracymentioning
confidence: 99%
“…Some researchers explored the relationship between these biases with cognitive abilities and thinking dispositions (e.g., Šrol & De Neys, 2021;Toplak & Flora, 2021;Toplak et al, 2014;West et al, 2008;Wyszynski & Diederich, 2023). At the same time, many studies on behavior, such as political behavior; on prediction of attitudinal variables, such as ethical dilemmas; on relationships with personality traits, such as conscientiousness; and health worries, such as COVID-related worries, have used human values in their investigations (e.g., Bojanowska & Urbańska, 2021;Fischer et al, 2021;Goren et al, 2022;Grosz et al, 2021;Klein & Ben Hador, 2021;Mubako et al, 2021).…”
mentioning
confidence: 99%